2021
DOI: 10.1155/2021/3459427
|View full text |Cite
|
Sign up to set email alerts
|

A Causal and Correlation Analysis between China Energy Futures and China Energy‐Related Companies Stock Market

Abstract: Taking the opportunity of China’s launch of Shanghai crude oil futures (INE), this study empirically examined the information transmission in this immature financial market, investigating this issue from a new perspective. To identify the impact of INE on the related stock market, we collected high-frequency trading data of oil futures and 22 stocks owned by listed companies in the upstream and downstream of China’s oil-related industry chains, constructed a causal chain through Directed Acyclic Graph, and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…In 2020, with the outbreak of COVID-19, the changes regarding the crude oil futures market during the epidemic have also attracted the interest of many scholars. Most scholars have uncovered the linkages and spillovers between world benchmark crude oil futures and other financial derivative markets during the epidemic, including gold, stock markets, cryptocurrencies, and crude oil spot [22][23][24][25]. Jefferson analyzed the impact of the epidemic on the oil industry in different countries and found that, despite a partial recovery, many oil industries will still suffer [26].…”
Section: Relationship Between Futures and Spot Marketmentioning
confidence: 99%
“…In 2020, with the outbreak of COVID-19, the changes regarding the crude oil futures market during the epidemic have also attracted the interest of many scholars. Most scholars have uncovered the linkages and spillovers between world benchmark crude oil futures and other financial derivative markets during the epidemic, including gold, stock markets, cryptocurrencies, and crude oil spot [22][23][24][25]. Jefferson analyzed the impact of the epidemic on the oil industry in different countries and found that, despite a partial recovery, many oil industries will still suffer [26].…”
Section: Relationship Between Futures and Spot Marketmentioning
confidence: 99%